The lived experience of a novel disruptive therapy in a group of men and boys with haemophilia A with inhibitors: Emi & Me - Fletcher, Simon; Jenner, Kathryn; Holland, Michael; Khair, Kate (Health expectations : an international journal of public participation in health care and health policy, 2022)
Background People with haemophilia A and inhibitors (PwHi) suffer more orthopaedic complications, bleeding and pain than those without inhibitors. The advent of emicizumab as a prophylactic treatment has led to a reduction in bleed frequency and a significant improvement in overall quality of life. No research to date has examined the nature of this improvement on treated individuals and their families. Aims The Emi & Me study aims to capture the real‐life experience of using emicizumab for PwHi and their families. Methods Participants were recruited through treatment centres, social media and by word of mouth. Each participant and a family member, if available, took part in a semistructured qualitative interview. All interviews were recorded, transcribed verbatim and analysed thematically. All elements of the study were reviewed by local statutory authorities and informed consent was sought from all participants. Results Fifteen PwHi, mean age 27.2 years (range 8–63 years), most with a family member, participated in a single qualitative interview online (n = 13), by telephone (n = 1) or in person (n = 1). Mean time on emicizumab was 2.26 years (range 1–5 years). Six major themes emerged: bleeds; pain; treatment burden; control; freedom (for both PwHi and family members) and missed potential. Emicizumab prophylaxis has delivered significant improvements in the lives of the participants. Despite these improvements, some participants felt that their pre‐existing physical disabilities and the lack of physiotherapy provision had prevented them achieving similar improvements in their functional ability. Conclusion This study shows that in reducing bleeds, pain and treatment burden, emicizumab had given PwHi greater control over their condition, allowing a sense of freedom they had not experienced with factor VIII or bypassing agent prophylaxis. However, for emicizumab to be truly effective, there is a need to ensure the continued availability and accessibility of robust multidisciplinary support services. Without this, it is unlikely that PwHi will realize the life‐changing potential offered either by emicizumab or any other novel treatment approach. Patient or Public Contribution A patient participant (who did not wish to be included as an author of the paper) was involved in the design of the study protocol and interview guide.